In-Hospital Outcomes and Temporal Trends of Surgical Versus Intravascular Ultrasound–Guided Endovascular Interventions for Femoropopliteal Disease - Elsayed, Basel (2025)
BackgroundPeripheral artery disease is a global health concern, with femoropopliteal disease being a common manifestation. Recent advancements in endovascular interventions (EVI), guided by intravascular ultrasound (IVUS), have introduced promising treatment options. This study aims to compare in-hospital outcomes and trends of surgical versus IVUS-guided EVI for femoropopliteal disease. MethodsThe National Inpatient Sample database (2016-2021) was analyzed. Procedures were identified using the International Classification of Diseases, Tenth Revision, Clinical Modification codes, and the Cochran-Armitage test was used to assess temporal trends. Propensity score matching balanced baseline characteristics between the surgical (weighted N = 6700) and IVUS-guided EVI (weighted N = 6700) groups. Multivariable regression analysis adjusting for matched covariates was conducted to compare outcomes. ResultsMultivariable logistic regression revealed that in-hospital mortality was lower in the IVUS-guided EVI group (1.6%) compared to the surgical group (3.5%) (OR, 0.386; 95% CI, 0.216-0.692). IVUS-guided EVI also had significantly fewer periprocedural complications (20.6% vs 24.7%; OR, 0.767; 95% CI, 0.636-0.924), including lower rates of bleeding, shock, infections, wound disruption, and respiratory failure. Multivariable linear regression showed that the length of stay was shorter for the IVUS-guided EVI group (β = –1.7 days; 95% CI, –2.2 to –1.1). No statistically significant differences were observed in inflation-adjusted costs, cardiac complications, major amputation, stroke, or renal failure. ConclusionsIntravascular ultrasound–guided EVI for femoropopliteal disease are associated with better in-hospital outcomes compared to surgical revascularization, including lower in-hospital mortality, periprocedural complications, and a shorter length of stay. However, future prospective studies are needed to validate these results.